PERAN INVESTASI TERHADAP PEREKONOMIAN DAERAH : STUDI KASUS DI KABUPATEN GARUT - Rahmawatin, Rahmawatin; Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
High economic growth shows an increase in productivity, the impact of which can increase employment opportunities. Besides increasing productivity can also increase community income, reduce unemployment and reduce poverty. One component of economic growth is investment, which is needed to increase productivity. The aims of this paper was to determine the description or condition of the investment climate in Garut Regency viewed from the ICOR value coefficient. The results showed that the ICOR value illustrates the efficiency of investment in an area. The ICOR value of Garut Regency in 2018 is 5.7. By using the standard method, the results show that investment in Garut Regency needs lag (t + 4) so that an investment reaches full capacity